SKRINING FITOKIMIA MINYAK ATSIRI AKAR WANGI (Vetiveria zizanioides (L.) Nash) ASAL KABUPATEN GARUT - Nurul, Nurul; Sujana, Dani; Nugraha, Yogi Rahman; Muharam, Firman; Puspitasari, Siva; Syswianti, Desy (Karsa Husada Health Institute Garut, 2024)
Indonesia is uniquely positioned among the countries in the world where most of the land consists of tropical forests. Besides Haiti and the Bourbon Pacific, Indonesia is among the three largest producers of vetiver oil in the world. Garut Regency is the center of vetiver oil production in Indonesia. Vetiver root (Vetiveria zizanoides L. Nash), is known to contain terpenoid compounds that have antioxidant bioactivity, especially ?-vetivena, ?-vetivenon, and ?-vetivenon compounds. Phytochemical screening is a way to determine the content of secondary metabolites in a natural material. This study aims to determine the content of secondary metabolites in vetiver essential oil from Garut Regency. This research is qualitative in nature using a descriptive design of laboratory experiment method. The vetiver essential oil produced by the steam distillation method was tested for secondary metabolite content using thin-layer chromatography by looking at the stains that appeared on the chromatogram and the Rf value of the tested compounds. Secondary metabolite compounds tested include alkaloids, flavonoids, tannins, steroids, terpenoids, and saponins. Vetiver essential oil contains steroid compounds characterized by the onset of blue stains with an Rf of 0.9 and terpenoid compounds characterized by the onset of bright blue stains with an Rf of 0.54.